Efektifitas Alokasi Dana Desa di Kenagarian Sungai Rimbang Kabupaten Lima Puluh Kota - Indah Gita Cahyuli (Journal of Civic Education, 2022)
This study aims to investigate the effectiveness of village fund utilization in Kenagarian Sungai Rimbang, Suliki District, Lima Puluh Kota Regency, and to identify potential areas for development as well as obstacles faced during the utilization of the village funds. The research method utilized was qualitative with a descriptive approach, and data validation was conducted using member check and source triangulation techniques. Data analysis was carried out through data reduction, presentation, and conclusion drawing. The findings of this study suggest that the utilization of village funds has not been maximized for village development, as the focus has been primarily on infrastructure development. The potential of this Nagari lies in rice farming and agriculture, and the funds should be allocated towards community empowerment. Several obstacles were identified in the process of utilizing the village funds, including the low skills of human resources in Nagari, an insufficient amount of village funds to cover development in all Jorong, and low support from the village community.